Impact of Y chromosome loss on the risk of Parkinson's disease and progressionResearch in context - Junhao Wang; Xinyi Chen; Wenxuan Du; Cha Lin; Yu Liao; Jean-Christophe Corvol; Jodi Maple-Grødem; Meghan C. Campbell; Alexis Elbaz; Suzanne Lesage; Alexis Brice; Michael A. Schwarzschild; et al. (EBioMedicine)
Summary: Background: Loss of Y chromosome (LOY), an age-related somatic mutation, is associated with various age-related diseases, but its role in the onset and progression of Parkinson's disease (PD) remains unclear. This study investigated the relationship between blood LOY levels and the risk of PD onset and progression. Methods: We estimated the LOY level for each male participant based on genome-wide arrays or whole genome sequencing data. We performed Cox proportional hazards regression analysis among 222,598 male participants in the UK Biobank and linear mixed model analysis involving 2574 male individuals with PD across 14 cohorts, encompassing 19,562 visits. In the Parkinson's Progression Markers Initiative (PPMI) cohort, we further compared brain structure using T1-weighted magnetic resonance imaging (MRI) scans, and carried out brain network functional connectivity analysis based on resting-state functional MRI (rs-fMRI) datasets. Additionally, we assessed the LOY status in single-nucleus RNA sequencing (snRNA-seq) data, which included 1,303,531 cells from 279 post-mortem samples across five brain regions, and performed temporal dynamic gene expression analysis. Findings: Male participants with LOY had a slightly higher risk of developing PD during follow-up (HR = 1·16, 95% CI = 1·01–1·34, P = 0·04). Among males affected by PD, LOY carriers experienced accelerated neurodegenerative progression, manifesting as more rapid motor impairment (P = 0·0072) and cognitive decline (P = 0·0005) compared to non-LOY carriers. Patients with PD carrying LOY also exhibited decreased network functional connectivity in certain brain regions. Notably, LOY cells were particularly enriched in microglia/immune and vascular/epithelial cells, and a subset of genes in LOY-Mic P2RY12 cells were associated with PD progression. Interpretation: This data-driven study highlights the potential association of LOY with the onset and progression of PD through the analysis of multi-scale data, including clinical phenotypes, brain neuroimaging maps, and molecular profiles from single-nucleus transcriptome across multi-brain regions. These findings suggest that LOY may be an accomplice to the onset and progression of PD. Funding: G.L.'s work is supported by the Shenzhen Fundamental Research Program (JCYJ20240813151132042), National Natural Science Foundation of China (32270701, 32470708), Young Talent Recruitment Project of Guangdong (2019QN01Y139), the Science and Technology Planning Project of Guangdong Province (2023B1212060018) and Shenzhen Key Laboratory for Systems Medicine in Inflammatory Diseases (ZDSYS20220606100803007). This study is supported by High-performance Computing Public Platform (Shenzhen Campus) of Sun Yat-sen University. C.R.S.'s work is supported by NIH grants NINDS/NIA R01NS115144, the U.S. Department of Defense, and the American Parkinson Disease Association Center for Advanced Parkinson Research. C.R.S.'s research work was funded in part by Aligning Science Across Parkinson's 000301 through the Michael J. Fox Foundation for Parkinson's Research (MJFF). The study was made possible in part by a philanthropic support for Illumina MEGA chip genotyping (to Brigham & Women's Hospital and C.R.S.). CHWG received funding support from an RCUK/UKRI Research Innovation Fellowship awarded by the Medical Research Council (MR/R007446/1; MR/W029235/1) and from the NIHR Cambridge Biomedical Research Centre (NIHR203312). The views expressed are those of the author(s) and not necessarily those of the NIHR or the Department of Health and Social Care. For the purpose of open access, the author has applied a CC BY public copyright licence to all Author Accepted Manuscripts arising from this submission.